INDEKS KEANEKARAGAMAN DAN KEMIRIPAN VEGETASI DI HUTAN SEKUNDER KAWASAN SUB DAS POWELUA KABUPATEN DONGGALA - Naharuddin Naharuddin (Agroland: Jurnal Ilmu-ilmu Pertanian, 2006)
The research was carried at Powelua river basin in District of Donggala Sub  with an aim of studying the diversity and similarity index of vegetation in the region. The research employed a line plot sampling method of a square form. This was done tracing a straight line crossing the contour lines. Results indicated that the diversity index in both young and old secondary forests were high, with an index value (H’) of 2.9 and 3.0, respectively. The two secondary forests had no similarity at all stand levels which included tree, pole, seedling and ground cover levels.